Pathways to Professionalism: Work Placement and Career Development of BS Medical Technology Graduates - Alcazar, Amanda Therese; Biaculo, Glazel Gladys; Endrinal, Elyza Rosel; Estabillo, Jerome; Leocadio, Mike Lenard; Somido, Ferdinand (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the work placement and career development of Bachelor of Science in Medical Technology graduates of the University of Perpetual Help–Dr. Jose G. Tamayo Medical University (UPH-DJGTMU) from academic years 2021–2025. Guided by the Input–Process–Output (IPO) framework, the study described the graduates’ demographic, educational, employment, and career development profiles and determined the relationships among competencies acquired, employment relevance, career development, employment challenges, and employment outcomes. A descriptive-correlational research design was employed involving 142 graduates selected through convenience sampling. Data were gathered using a researcher-developed, content-validated graduate tracer study questionnaire administered through online and printed survey forms. Descriptive statistics, Spearman’s rank-order correlation, Chi-square test of independence, Kruskal–Wallis test, and One-Way ANOVA were used for data analysis. Findings revealed that most graduates secured employment within one to three months after graduation, were employed full-time in private healthcare institutions, and held positions in hospitals and diagnostic or clinical laboratories. Critical thinking, communication, and laboratory skills were identified as the most useful competencies acquired from the program, while low salary offers, limited job opportunities, and lack of work experience were the most common employment challenges. Significant positive relationships were found between employment relevance and career development activities, employment relevance and monthly salary, and competencies acquired with employment status and employment relevance. Employment challenges were significantly associated with time before employment and salary level. The study concluded that the BS Medical Technology program effectively prepared graduates for employment and professional growth. It recommends strengthening competency-based instruction, expanding industry partnerships, enhancing career support services, and encouraging continuing professional development and specialization to further improve graduate employability. The study supports Sustainable Development Goal (SDG) 4: Quality Education by promoting quality higher education that enhances graduate readiness for professional practice and SDG 8: Decent Work and Economic Growth by improving graduate employability and workforce participation. Its sustainability impact lies in strengthening institutional quality assurance, supporting workforce development in the healthcare sector, and informing evidence-based curriculum enhancement and career support initiatives.
Keywords: Career Development; Clinical Laboratory Science; Employability; Graduate Tracer Study; Higher Education Outcomes; Medical Technology Graduates